The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.18502/jovr.v16i3.9438
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Manifestations of the Sturge–Weber Syndrome

Abstract: Sturge–Weber syndrome (SWS) or encephalotrigeminal angiomatosis is a non-inherited congenital disorder characterized by neurologic, skin, and ocular abnormalities. A somatic activating mutation (R183Q) in the GNAQ gene during early embryogenesis has been recently recognized as the etiology of vascular abnormalities in SWS. Approximately, half of the patients with SWS manifest ocular involvement including glaucoma as the most common ocular abnormality followed by choroidal hemangioma (CH). The underlying pathop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 94 publications
0
19
0
4
Order By: Relevance
“…In our case, the patient was diagnosed with glaucoma in his early 20s and he was treated surgically with a valve implant. Since he had no clinical follow-up till this presentation, his left eye IOP returns to elevate, which indicates the failure of the surgery, like other studies that showed unfavorable outcomes in these patients [ 3 , 5 ].…”
Section: Discussionmentioning
confidence: 82%
“…In our case, the patient was diagnosed with glaucoma in his early 20s and he was treated surgically with a valve implant. Since he had no clinical follow-up till this presentation, his left eye IOP returns to elevate, which indicates the failure of the surgery, like other studies that showed unfavorable outcomes in these patients [ 3 , 5 ].…”
Section: Discussionmentioning
confidence: 82%
“…It is characterized by capillary–venous malformation of the brain, glaucoma, seizure, and neurological, ocular, and skin anomalies. Among the latter, port wine facial birthmarks stand out [ 62 , 63 , 64 , 65 , 66 ]. The etiology of this condition is attributed to somatic mutations that activate genes that encode heterodimeric G-protein chains, specifically the GNB2 gene, tha encodes the beta chain or the GNAQ and GNA11 genes that encode the alpha chain.…”
Section: Resultsmentioning
confidence: 99%
“…Although clinical data may be useful in this process, such data are not entirely decisive, given that at a clinical level there may be silent courses, as in the cases of CCT [ 58 ] and small CAs [ 31 ] or clinical manifestations that are closely similar, such headaches and seizures that are present in most of the different vascular malformation cases [ 17 , 20 , 32 , 33 , 49 , 50 , 51 , 60 , 62 , 68 ]. An example of a fairly useful clinical feature is port wine stain in the case of SWS [ 63 , 64 , 65 ]; however, this syndrome will only occur in 8% to 33% of the subjects with the skin mark [ 70 ]. In addition, SWS may be present without the presence of port wine stain.…”
Section: Discussionmentioning
confidence: 99%
“…Sturge-Weber Syndrome (SWS), a rare congenital angiomatosis, simultaneously involving the skin, mucous membrane, brain, and/or eyes, gives rise to a neuro-cutaneous syndrome of variable clinical presentation, resulting from mutation of the GNAQ gene. 4,5 The clinical features are often categorized to type I, type II, and type III according to the Roach scale (Table 1). Type I is called the classical type and Type III is the rarest type.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Its overall prevalence is 1 in every 20-50,000 live births and from an embryologic point of view, it results from non-regression of the cephalic part of the primitive venous plexus around the fetal neural tube. 4,5 As depicted by Shirly et al, SWS occurs due to somatic activating mutation in the GNAQ on the 9 th chromosome. However, it develops sporadically and lacks a specific inheritance pattern.…”
Section: Introductionmentioning
confidence: 99%